Morphometric study of sacrum in sex determination in Telengana region people - Maddikunta, Vasantha; Ravinder, M. (International Journal of Research in Medical Sciences, 2017)
Assessment of sex of the bone comes under the Canopy of Forensic Anthropology, which has it’s main roots in anatomy. Hence sound knowledge of anatomy particularly morphometric data is essential for identification of sex, race and region. Bones of pelvic girdle play key role for determination of sex. In addition to hip bones, sacrum also has it’s own importance in determination of sex. Hence in this study we have taken various parameters (maximum length of sacrum, maximum breadth of sacrum, Curved length of sacrum, transverse diameter of S1) and different indices (sacral index, curvature index, corpobasal index). From the above parameters and indices we have extracted demarcating points for each, which have statistical significant role in determining the male and female sex, which were discussed in detail in this publication.